INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH - Jumabayeva Mahliyo Ro'zmat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: the role and the effective usage of innovative technologies in teaching English are considered in this article. The Internet links, which are effectively used during the lessons, are also shown here.